Bianchi type-VI0 cosmological models in certain theories of gravitation - Ram S.; Singh P. (My University, 2025)
Exact Bianchi type-VI0 cosmological solutions to Einstein's equations are presented in vacuum and for stiff-matter in the normal gauge for Lyra's geometry and in scalar-tensor theories developed by Saez and Ballester (1985) and Lau and Prokhovnik (1986). Also cosmological solutions are obtained for pure massive strings (p-strings) and for pure geometric strings. The dynamical behaviour of the models have been discussed. © 1993 Kluwer Academic Publishers.